Family tree - Wiggs, Susan (HarperCollins, 2016)
Love. Success. A handsome husband, a beautiful home. These are the things Annie Rush can call her own. These are the foundations of her charmed life in Los Angeles. But in an instant, that life is shattered. And as Annie sifts through the ashes, she must face the shock and pain of a devastating loss. Grieving and wounded, she retreats to her family home in Switchback, Vermont, a maple farm generations old. There, surrounded by her free-spirited brother, their divorced mother, and four young nieces and nephews, Annie slowly emerges into a world she left behind years ago: the place where she grew up, the people she knew before, the hometown boyfriend whose life has been filled with unexpected turns. And with the discovery of a cookbook her grandmother wrote in the distant past, Annie unearths an age-old mystery that might prove the salvation of the family farm.